Antibacterial and anti-biofilm activity of cinnamon essential oil and eugenol - Millezi,Alessandra Farias (2019)
ABSTRACT: Biofilms are responsible for most of the interference caused by microorganisms in food processing. The aim of this study was to evaluate the cinnamon (Cinnamomum zeylanicum) essential oil and eugenol sanitizer and anti-biofilm activity against biofilms. Concentrations used of essential oil were 0.0% (control) 0.12%; 0.48%; 0.96% and 1.92%; the amount of eugenol was 0.76%. Concentrations were determined from other published studies. Number of viable cells and quantification the bacterial biomass were determined. Anti-biofilm treatment was effective in preventing the formation of biofilms. The 1.92% concentration was the most satisfactorily with Escherichia coli reduction of 5.91log CFUcm-2 and Staphylococcus aureus reduction of 5.17log CFUcm-2 (P<0.05) biomass of the two bacteria. Sanitizing treatment was not effective in reducing biomass. Seen this, the cinnamon and eugenol essential oil may be promising alternatives for controlling biofilms.